Effect of Job Training and Work Competency on Employee Performance through Job Satisfaction as a Mediating Variable: Case Study at the Cilegon City Communication, Informatics, Coding and Statistics Office - Shabrina, Alifah; Prahiawan, Wawan; Imron, Ali; Hilaldi, Dika (PT. Riset Press International, 2025)
This study aims to test and analyze the effect of Job Training and Job Competencies on Employee Performance through mediation of Job Satisfaction at the Cilegon City Communication, Informatics, Coding and Statistics Office. The research method used is quantitative research method with descriptive approach. This research collects data based on literature studies, interviews, observations and distributing questionnaires. The population in this study were employees of the Cilegon City Communication and Information Office with a research sample of 62 respondents. The data analysis method used is Structural Equation Modeling (SEM) with the SmartPLS 4.1.1.4 analysis tool. This study has the results that: (1) Job Training has a positive and significant effect on Employee Performance. (2) Job Competency has a positive and significant effect on Employee Performance. (3) Job Training has a positive and significant effect on Job Satisfaction. (4) Job Competence has a positive and significant effect on Job Satisfaction. (5) Job Satisfaction has a positive and significant effect on Employee Performance. (6) Job Satisfaction is able to mediate Job Training with Employee Performance. (7) Job Satisfaction is able to mediate Job Competency with Employee Performance.